Domestikasi Berbalut Pemberdayaan Perempuan pada Kegiatan Kawasan Rumah Pangan Lestari (KRPL) di Kabupaten Sidoarjo - Munari Kustanto (UIN Raden Mas Said Surakarta, 2017)
The problem of food security is becoming one of the important issues not only in Indonesia but also in the world. This is apparent from the lifting of the food problem as one of the SDGs intention. In an effort to realize food security the Government initiate activities KRPL with women as the target. The empowerment strategy is carried in this activity indicated by not freeing women but instead perpetuate the hegemony patriarchy. This research seeks to elaborate on how the culture works with patriarchy wrap women's empowerment in KRPL to perpetuate its hegemony through domestication. This research used the qualitative approach, both in gathering techniques as well as data analysis. The required data in the study gained through the study of literature and in-depth interviews. Empowerment activities in KRPL carried no more patriarchy culture in an effort to perpetuate its hegemony. Practices KRPl on the field it is pushed on a domestication against women. Construction on the role of women in domestic activities is supported by regulations that underlie KRPL implementation.Domesticated which happens to female cannot be released from the use of WID approach by the government.